Impact of Occlusal Schemes on Implant-Supported Overdentures - Rene Kuriakose; Achuthan Nair; Malak S. Bamigdad; Deepika R. Pai; Nadeem A. Rahman; Lino Paul (Journal of Pharmacy and Bioallied Sciences)
Background: The occlusal scheme is a crucial factor in the success and patient satisfaction of implant-supported overdentures. Different occlusal schemes, such as balanced, lingualized, and monoplane occlusion, can influence the functional and biomechanical outcomes. Materials and Methods: A randomized controlled trial was conducted with 60 edentulous patients who received mandibular implant-supported overdentures. The patients were divided into three groups based on the occlusal scheme: Group A (balanced occlusion), Group B (lingualized occlusion), and Group C (monoplane occlusion), with 20 patients in each group. All patients received two implants in the mandibular canine regions. The overdentures were fabricated and adjusted according to the assigned occlusal scheme. Clinical assessments, including bite force measurement and masticatory efficiency, were performed at baseline, 3 months, and 6 months post-insertion. Patient satisfaction was evaluated using a validated questionnaire. Results: At 6 months, Group A (balanced occlusion) exhibited the highest mean bite force (200 N ± 20), followed by Group B (lingualized occlusion) with 180 N ± 15, and Group C (monoplane occlusion) with 160 N ± 10. Masticatory efficiency was significantly higher in Group A (80% ± 5) compared to Group B (75% ± 4) and Group C (70% ± 3). Patient satisfaction scores were highest in Group A (9.0 ± 0.5), followed by Group B (8.5 ± 0.4) and Group C (8.0 ± 0.3). There were statistically significant differences between the groups in terms of bite force, masticatory efficiency, and patient satisfaction (P < 0.05). Conclusion: Balanced occlusion provided superior functional outcomes and higher patient satisfaction for implant-supported overdentures compared to lingualized and monoplane occlusion schemes.